HBV reactivation and its effect on survival in HBV-related hepatocarcinoma patients undergoing transarterial chemoembolization combined with tyrosine kinase inhibitors plus immune checkpoint inhibitors - Shen, Jiaming; Wang, Xia; Wang, Ningning; Wen, Shifei; Yang, Guangde; Li, Li; Fu, Juanjuan; Pan, Xiucheng (Frontiers in Cellular and Infection Microbiology, 2023)
Objective This study aimed to access hepatitis B virus (HBV) reactivation and its effect on survival in HBV-related hepatocarcinoma (HCC) patients who underwent transarterial chemoembolization (TACE) combined with tyrosine kinase inhibitors (TKIs) plus immune checkpoint inhibitors (ICIs). Methods In this single-center retrospective study, we enrolled 119 HBV-related unresectable advanced HCC patients receiving TACE combined with TKIs plus ICIs. Risk factors for HBV reactivation were analyzed by logistic regression. Kaplan-Meier method was applied to draw the survival curve, and log-rank test was used to compare survival between patients with and without HBV reactivation. Results A total of 12 patients (10.1%) encountered HBV reactivation in our study, of which only 4 patients received antiviral prophylaxis. The incidence of HBV reactivation was 1.8% (1/57) in patients with detectable baseline HBV DNA and 4.2% (4/95) in patients with antiviral prophylaxis respectively. Lack of prophylactic antiviral treatment (OR=0.047, 95%CI 0.008-0.273, P=0.001) and undetectable HBV DNA (OR=0.073, 95%CI 0.007-0.727, P=0.026) were independent risk factors for HBV reactivation. The median survival time (MST) for all patients was 22.4 months. No survival difference was observed in patients with or without HBV reactivation. (MST: undefined vs 22.4 months, log-rank test: P=0.614). Conclusion HBV reactivation could occur in HBV-related HCC patients who treated with TACE in combination with TKIs plus ICIs. Before and during the combination treatment, it is necessary to routinely monitor HBV DNA and to take effective prophylactic antiviral therapy.